Lysine-specific histone demethylase 1 inhibition enhances robust fetal hemoglobin induction in human β0-thalassemia/hemoglobin E erythroid cells - Woratree Kaewsakulthong (2022)
Induction of fetal hemoglobin (HbF) ameliorates the clinical severity of β-tha-lassemias. Histone methyltransferase LSD1 enzyme removes methyl groups from the activating chromatin mark histone 3 lysine 4 at silenced genes, including the γ-globin genes. LSD1 inhibitor RN-1 induces HbF levels in cultured human erythroid cells. Here, the HbF-inducing activity of RN-1 was investigated in erythroid progenitor cells derived from β0-thalassemia/ hemoglobin E (HbE) patients. The significant and reproducible increases in γ-globin transcript and HbF expression upon RN-1 treatment were demonstrated in erythroid cells with divergent HbF baseline levels, the average of HbF induction was 17.7±0.8%. RN-1 at low concentration did not affect viability and proliferation of erythroid cells, but decreases in cell number were observed in cells treated with RN-1 at high concen-tration. Delayed terminal erythroid differentiation was revealed in β0-thalassemia/HbE erythroid cells treated with RN-1 as similar to other compounds that target LSD1 activ-ity. Downregulation of repressors of γ-globin expression; NCOR1 and SOX6, was observed in RN-1 treatment. These findings provide proof of the concept that LSD1 epigenetic enzyme is a potential therapeutic target for β0-thalassemia/HbE patients.